2005
DOI: 10.1159/000086419
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity and Immunocrossreactivity of Orange Tree Pollen and Orange Fruit Allergenic Extracts

Abstract: Background: It is important to study the crossreactivity between orange tree pollen (OTPE) and orange fruit (OFE) due to the high incidence of pollen/food-related allergies worldwide. The aim of the present study was to determine the antigenic relationship between OTPE and OFE. Methods: OTPE and OFErabbit antisera as well as sera from patients allergic to OTPE and OFE were comparatively applied in IgG- and/or IgE-specific ELISA inhibition, crossover or inhibition immunoblotting assays using OTPE and OFE allerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Many plant pollens from fruit trees are entomophilous and therefore considered of low allergenic interest, except for subjects occupationally exposed [3,4]. Cases of allergic reactions to pollen from fruit trees and ornamental plants have been reported, although mainly limited to workers directly exposed or pollen that is transported by airborne particles [5][6][7][8][9]. However, in certain regions of the world fruit tree pollens can be relevant not only in exposed individuals but also in the general population, as occurs with palm tree pollen [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many plant pollens from fruit trees are entomophilous and therefore considered of low allergenic interest, except for subjects occupationally exposed [3,4]. Cases of allergic reactions to pollen from fruit trees and ornamental plants have been reported, although mainly limited to workers directly exposed or pollen that is transported by airborne particles [5][6][7][8][9]. However, in certain regions of the world fruit tree pollens can be relevant not only in exposed individuals but also in the general population, as occurs with palm tree pollen [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In certain cases, pollens from cultivated and non-cultivated plants can be relevant for subjects exposed at different agricultural sites [4,5]. In the case of cultivars of fruit trees, although entomophilous, pollen grains can be transported by the wind for short distances [9,13]. This transport can be facilitated by the presence of pollutants or the disruption of pollen in smaller submicronic particles [2].…”
Section: Introductionmentioning
confidence: 99%
“…Other examples of IgE cross-reactivity include pollen–food allergy, such as apple–birch allergy or pollen–fruit allergy ( 249 – 253 ), dog–cat allergy ( 254 , 255 ), poultry–meat allergy ( 256 ), fish–chicken allergy ( 257 ), birch–oak allergy ( 258 ), latex–hymenoptera allergy ( 239 – 241 ). IgE cross reactivity to latex and parasites like Schistosoma has also been described ( 259 , 260 ).…”
Section: Gaps Of Knowledge Unmet Needs and Unanswered Questionsmentioning
confidence: 99%
“…Pollen from Fagales has been shown to be of high clinical impact due to airborne pollination. In contrast, it was assumed, that inhalation of insect-borne fruit tree pollen is only limited to people having a very close contact to fruit trees in the context of occupational exposure (Iraneta et al, 2005). Monitoring of Rosaceae pollen across Europe during the past 30 years, showed a moderate, but constant exposure.…”
Section: Discussionmentioning
confidence: 99%
“…First studies in fact revealed similar IgE cross-reactivity among the pollen proteins of birch and apple trees (Berrens, van Dijk, Houben, Hagemans, & Koers, 1990). Recently significant IgE-mediated allergy to papaya and orange tree pollen was demonstrated as a consequence of occupational fruit pollen exposure (Blanco et al, 1998;Iraneta et al, 2005).…”
Section: Introductionmentioning
confidence: 99%